NEW ANALYTICAL TECHNIQUES FOR THE IDENTIFICATION OF PLANT CONSTITUENTS AND FOR THE QUALITY ASSESSMENT OF HERBAL MEDICINES - Hostettmann, K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Plants represent an extraordinary reservoir of novel molecules and there is currently a resurgence of interest in the vegetable kingdom as a possible source of new lead compounds for introduction into screening programs. Plant constituents of interest are usually isolated following a bioactivity-guided fractionation procedure. In order to render this approach more rapid and efficient, the dereplication of crude plant extracts with LC-hyphenated techniques represents a strategic element to avoid finding known constituents and to target the isolation of new bioactive compounds In order to obtain direct spectroscopic information on-line, from crude plant extracts, hyphenated techniques such as HPLC coupled to UV photodiode array detection (LC-DAD/UV), to mass spectrometry (LC/MS) and to nuclear magnetic resonance (LC/NMR) have been investigated. In our laboratory, these techniques have been fully integrated into the isolation process and are used for the chemical screening of crude plant extracts. As a complement to this approach, capillary NMR (CapNMR) can be performed. Since the volume of the CapNMR probe is 5 µl, very small samples can be analysed. When combined with bioassays performed after LC/microfractionation of extracts, on-line identification of bioactive compounds is possible. Examples of rapid localisation of bioactive compounds will be given, together with the potential of hyphenated techniques for the quality control of herbal medicines.